2010
DOI: 10.3390/toxins2071848
|View full text |Cite
|
Sign up to set email alerts
|

The Enterotoxicity of Clostridium difficile Toxins

Abstract: The major virulence factors of Clostridium difficile infection (CDI) are two large exotoxins A (TcdA) and B (TcdB). However, our understanding of the specific roles of these toxins in CDI is still evolving. It is now accepted that both toxins are enterotoxic and proinflammatory in the human intestine. Both purified TcdA and TcdB are capable of inducing the pathophysiology of CDI, although most studies have focused on TcdA. C. difficile toxins exert a wide array of biological activities by acting directly on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
146
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(152 citation statements)
references
References 209 publications
(262 reference statements)
1
146
0
5
Order By: Relevance
“…Previously, the role of many chemokines and proinflammatory mediators in TcdA-induced enteritis has been studied individually with ileal loops or in vitro (27). For example, Morteau et al found increased Ccl3 and Ccl5 transcription in whole tissue 1 h after TcdA injection and showed that Ccl3 knockout mice were less susceptible to TcdA (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the role of many chemokines and proinflammatory mediators in TcdA-induced enteritis has been studied individually with ileal loops or in vitro (27). For example, Morteau et al found increased Ccl3 and Ccl5 transcription in whole tissue 1 h after TcdA injection and showed that Ccl3 knockout mice were less susceptible to TcdA (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been difficult to tease apart the aspects of the host response to TcdA and TcdB because of the important interactions among the many tissues, cell types, and signals involved (27,28). The intestinal epithelium, the initial barrier to these toxins, continuously interacts with surrounding cells throughout the development and resolution of disease.…”
mentioning
confidence: 99%
“…Together, these inflammation-related activities contribute to the progressive ablation of gastrointestinal function that is characteristic of CDI. In animal models, the administration of purified C. difficile TcdA induces the hallmark symptoms of an acute, pseudomembranous colitislike condition: edema, gastrointestinal inflammation, cellular necrosis, and gastroenteritis in the absence of the bacterium (19,(21)(22)(23). The administration of TcdB elicits similar effects, albeit to a lesser degree (22,24).…”
mentioning
confidence: 80%
“…The main virulence factors of C. difficile are represented by two exotoxins, toxin A (TcdA) and toxin B (TcdB), similar in structure and mechanisms of action [47] (although TcdB is about 1000-fold more potent than TcdA [48]). Both toxins are able to cause adverse effects in enteric cell populations, such as enterocytes, colonocytes, and enteric neurons [47,49].…”
Section: Pi-ibs After C Difficile Infection: a Case Of A Microbiologmentioning
confidence: 99%
“…Both toxins are able to cause adverse effects in enteric cell populations, such as enterocytes, colonocytes, and enteric neurons [47,49].…”
Section: Pi-ibs After C Difficile Infection: a Case Of A Microbiologmentioning
confidence: 99%